Estudo sobre alvenaria estrutural com blocos de concreto - Hashiguti, Akemy Alyne (2018)
Constructions in Structural Masonry aim to be more advantageous than conventional constructions. Nowadays they are largely used, because when this system are adequately designed and executed it is more feasible as regards the economic question, and for this an extreme quality construction management is required and consequently better results will be achieved. The Concrete Blocks, in turn, improve the construction standards, allow aesthetic details, have greater thermal, acoustic and fire resistance. Many professionals who execute or supervise the civil works do not know about the peculiarities of this kind of edification, what make them loose space for the capacity professionals who work in intelligent and strategic projects using concrete blocks. Materials, equipment and applications need to be used in order to have proper practice of implementing such a system, due to the many specificities and techniques required. Having a construction planning means to avoid losses and to bring forward the course of the civil works, moreover, a planned project is more practical and easy for execution and control. Several entrepreneurs are betting on this Construction System of concrete blocks seeking technical and agile civil works, with reduced expenses, high-quality products and a satisfactory final result.